PROJECT MANAGEMENT ON THE BASIS OF BUILDING SIMULATION - Druzhinin А.; Druzhinin Е.; Davydenko О.; Obukhova, N. (Municipal economy of cities. Series: «Economy science», 2023)
The problems of the strategy and tactics of European integration in the innovative development of the construction complex of Ukraine have led to the need for transformation in modern conditions through large infrastructure projects, increasing the residual resources of facilities and the transition of the industry to the use of new BIM technologies. Building information modeling is a technology for optimizing the processes of designing, constructing, and operating a building, based on the use of a single model and the exchange of information on any object between all participants throughout the entire life cycle - from the owner’s idea and the architect’s first sketches to the maintenance of the finished building. Project management is a purposeful, continuous process of coordinating the actions of the participants in the formation and implementation of a project in order to produce products in the optimal time frame and maximize profits. In a market economy, the actions of project participants are often opposite, and the task of management is to subordinate their activities to the investor’s single goal. The investor wants to get the project cheaper and faster. The contractor wants to build it in a favorable time frame with maximum profit. Management considers the project as a dynamic system in which different subsystems operate at different stages of the life cycle. The leading management function is strategic and tactical planning, and the central function in operational management is regulation. Based on the principles and mechanism of project life cycle management, the implementation of BIM technology requires solving a number of problems and creating prerequisites related to design, construction, and operation. The analysis and evaluation of the economic efficiency of the system at each level and in general should be preceded by scenario design - the selection of the optimal scenario from several technically feasible, competing options for the project life cycle. The adopted methodological approach and variant design as part of BIM technology involves our research to improve the analysis and evaluation of the efficiency of production organization in design and construction from the standpoint of a system of models and methods of structural optimization in the innovative development of the construction complex of Ukraine in difficult market conditions. The assessment of the economic effect over the life cycle of an object using BIM technology should be investigated according to a scheme where several options for the design of the object should be developed with the final decision. At the same time, BIM technology involves predicting the risks of changes in the conditions of actual construction and operation of the facility, repair systems, and cost-effectiveness assessment over the life cycle of the project. The introduction of a BIM system into the design and construction process has undeniable advantages, as it allows you to instantly access any information about the facility, control the quality of work at all stages, avoid conflicts in the project, and significantly reduce the cost of construction.